An Evaluation On Penang Hospital Pharmacists, Community Pharmacists, And Consumers’ Perception Toward The Implementation Of Zoning Of Community Pharmacies In Penang, Malaysia - Leong, Pui Chee (2024)
Over the years, the zoning policy regarding community pharmacies has stirred controversy in malaysia. Despite being widely adopted in many countries, such policies have yet to be implemented in malaysia. This study aimed to assess in depth opinion of hospital pharmacists, community pharmacists and consumers regarding zoning of community pharmacies in malaysia. A semi-structured qualitative study utilising face-to-face interviews was carried out in april to september 2021 among 11 hospital pharmacists (aged 31 to 40 years), 12 community pharmacists (aged 31 to 40 years) and 10 consumers (aged 27 to 48 years old) in penang, malaysia. Purposive sampling was employed, and data collection was stopped when the saturation point was reached. The interviews were audio-recorded and transcribed verbatim. The transcripts were independently coded and verified by experts with the resultant data analysed by atlas.Ti version 8 using thematic analysis. The study found that hospital pharmacists and consumers have lack of exposure to the concept of zoning policy. All the three respondent groups were aware about the oversaturation of community pharmacies in urban areas as compared to rural areas. They believed that many pharmacists refused to establish their stores in rural areas because of hard to survive in business.